Collaboration: Teaching Laboratory Medicine Across Disciplines. - PETERSON, KAREN (Clinical Laboratory Science)
Medical laboratory results are used to aid in patient diagnosis and treatment; however, advanced-practice practitioners have minimal training in the laboratory discipline. The University of North Dakota's Medical Laboratory Science program and the Family Nurse Practitioner (FNP) program have developed a collaboration to foster the effective application of laboratory results to aid in patient diagnosis and treatment. The FNP program has incorporated two 3-hour blocks in their curriculum to cover medical laboratory content that includes the topics of urinalysis, body fluids, hematology, and microbiology. Specifically for microbiology, content was present by breaking down the results of the laboratory report and focusing on how the laboratory obtained the results for each stage (ie, preliminary report) of the report. After the presentation, the students were surveyed using Qualtrics, and it was concluded that the information covered during the laboratory sessions influenced how they interpret laboratory results, which leads to more efficacious treatment and better patient care.